Trading Places : Accessing land in African cities - Napier, Mark (Book collections on Project MUSE., 2013)
Trading Places is about urban land markets in African cities. It explores how local practice, land governance and markets interact to shape the ways that people at society's margins access land to build their livelihoods. The authors argue that the problem is not with markets per se, but in the unequal ways in which market access is structured. They make the case for more equal access to urban land markets, not only for ethical reasons, but because it makes economic sense for growing cities and towns. If we are to have any chance of understanding and intervening in predominantly poor and very.